Novel in vivo screening design for the rapid and cost‐effective identification of transcriptional regulators. Issue 1 (6th March 2017) - Hellmann, Eva; Swinka, Christine; Heyl, Alexander
Abstract : Genetic screens are a common tool to identify new modulators in a defined context, e.g. hormonal response or environmental stress. However, most screens are either in vitro or laborious and time‐and‐space inefficient. Here we present a novel in planta screening approach that shortens the time from the actual screening process to the identification of a new modulator and simultaneously reduces space requirements and costs. The basic features of this screening approach are the creation of luciferase reporter plants which enable a non‐invasive readout in a streamlined multiplate reader process, the transformation of those plants with an inducible, Gateway™‐compatible expression vector, and a screening setup, in which whole plants at the seedling stage are screened in 96‐multiwell plates in the first transformed generation without the use of an expensive charge‐coupled device (CCD) camera system. The screening itself and the verification of candidates can be done in as little as 2–3 weeks. The screen enables the analysis of reporter gene activity upon different treatments. Primary positive plants can immediately be selected and grown further. In this study a fast, simple, cost‐ and space‐efficient in planta screening system to detect novel mediators of a given transcriptional response was developed and successfully tested using the cytokinin signal transduction as a test case.